Does Crown Financial Portfolio Composition Matter? - Nick Davis (New Zealand Government, The Treasury, 2001)
This paper considers Crown financial portfolio composition from a welfare perspective. It argues that a broad definition of the Crown's portfolio is required for analysing the welfare implications of portfolio composition. In practice, this means incorporating the present discounted value of tax and expenditure flows as well as traditional measures of assets and liabilities. Financial portfolio composition affects welfare for a number of reasons: imperfect and incomplete markets; distortionary taxes; externalities; and agency problems. There is unlikely to be a single policy objective for choosing the preferred portfolio composition that integrates all of those factors. However, it is argued that the Crown should be risk averse and aim to eliminate all diversifiable risk in its portfolio. There is a reasonable case for adopting a low-risk Crown portfolio. Importantly, that does not necessarily require a low-volatility financial portfolio.
Keywords: H11; H63; 330; Public Finance; Portfolio Management